A differential DNA methylome signature of pulmonary immune cells from individuals converting to latent tuberculosis infection - Karlsson L. (2021)
We would like to show our appreciation to the medical personnel at Instituto de Medicina Tropical Alexander von Humboldt, Universidad Peruana Cayetano Heredia, for assistance in sample collections and analysis of QuantiFERON® TB-Gold Plus test. We thank the Bioinformatics and Expression Analysis core facility (BEA) at Karolinska Institute that preformed the sequencing analysis. We thank the Swedish National Infrastructure for Computing (SNIC) at National Supercomputing Centre (NSC), Linköping University for the computing systems enabling the data handling, partially funded by the Swedish Research Council through grant agreement No. 2018-05973. The work was supported by grants from the Swedish Research Council No. 2018-04246 and the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica CONCYTEC and Cienciactiva No. 106-2018-FONDECYT. J.D is a postdoctoral fellow supported through the Medical Infection and Inflammation Center (MIIC) at Linköping University.